Tanggung Jawab Sektor Industri terhadap Pengolahan Limbah B3 Berdasarkan UU Perlindungan dan Pengelolaan Lingkungan Hidup - Arianto, Marwan; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Industrial growth has substantially contributed to economic development while simultaneously increasing the risk of environmental pollution through the generation of hazardous and toxic waste (B3 waste). Improper management of B3 waste threatens environmental sustainability, public health, and natural resources, making effective legal regulation essential. This study examines the legal responsibility of the industrial sector in managing B3 waste under Indonesian environmental law, particularly Law Number 32 of 2009 on Environmental Protection and Management and its implementing regulations. The research employs a normative juridical method using statutory, conceptual, and limited case approaches. Primary legal materials include the 1945 Constitution, Law Number 32 of 2009, relevant government regulations, and ministerial regulations concerning B3 waste management, while secondary materials consist of books, scientific journals, and previous studies. The findings indicate that industrial responsibility extends beyond technical waste management activities, encompassing environmental licensing, monitoring, reporting, and preventive risk management. Violations may result in administrative, civil, or criminal liability depending on the nature and impact of the offense. Although the existing legal framework provides a comprehensive basis for environmental protection, its implementation remains constrained by weak supervision, inconsistent compliance, limited institutional capacity, and challenges in law enforcement. Strengthening regulatory oversight, institutional coordination, and consistent enforcement is therefore essential to ensure effective B3 waste management and achieve sustainable environmental governance..